Analysis of dynamic failure characteristics and gas seepage law of gas-bearing coal under impact loads - Dengke WANG; Liyuan ZHANG; Jianping WEI; Hailong DU; Zhen LI; Zhiming WANG; Bowen DONG; Fukai ZHANG; Yanbo YIN; Hongtu ZHANG; Yanzhao WEI (Meitan xuebao, 2024)
Using an impact damage-percolation experimental system for gas-bearing coal or rock, the authors carry out various gas-bearing coal impact experiments with in-situ seepage tests to reveal the law of dynamic mechanical characteristics, fracture expansion, and permeability changes of gas-bearing coal under different impact loads and gas pressures loading. Using an industrial CT scanning system, the authors conduct a 3D reconstruction of the fracture structure in order to analyze the internal fracture expansion characteristics of gas-bearing coal and the influence law on gas permeation patterns. The results show that both the impact load and gas pressure play an important role in the dynamic mechanical properties, deformation process, fracture expansion, and gas permeation patterns of gas-bearing coal: ① Under the coupling of impact load and gas pressure, the stress-strain curve of gas-bearing coal has an inconspicuous compaction stage due to the influence of confining pressure and axial pressure. The deformation process of gas-bearing coal includes elastic deformation stage, strain strengthening stage, and failure stage. ② The increase of impact load will increase the dynamic mechanical parameter value of gas-bearing coal, while the increase of gas pressure will reduce the value. The greater the impact load, the higher the gas pressure, and the more sufficient the fracture expansion of gas-bearing coal. At the same time, the fracture structure is more complex. ③ The seepage law of gas-bearing coal is controlled by fracture expansion. Under the coupling of impact load and gas pressure, three types of gas flow exist in gas-bearing coal: pore flow, coexistence of pore flow and fracture flow, and fracture flow. After the impact failure of gas-bearing coal, the gas flow pattern can transition from pore flow to coexistence of pore flow and fracture flow, and eventually to fracture flow, as the gas pressure increases and the influence of gas wedges intensifies. Fracture expansion and flow patterns jointly affect the seepage law of gas-bearing coal. The permeability of gas-bearing coal generally exhibits a trend of initially increasing and then decreasing with the increase of gas pressure.